Purification and Identification of Novel Antioxidant Peptides Isolated from Geoffroea decorticans Seeds with Anticoagulant Activity - Juliana Cotabarren; Brenda Ozón; Santiago Claver; Javier Garcia-Pardo; Walter David Obregón (MDPI AG, 2021)
Geoffroea decorticans is a xerophilous deciduous tree present in most arid forests of southern South America, which is commonly used in traditional medicine. The seeds of this tree have been previously investigated for their singular chemical composition, but their protein content has been poorly investigated. Herein, we report the isolation, purification, and characterization of a set of thermostable peptides derived from Geoffroea decorticans seeds (GdAPs) with strong antioxidant and anticoagulant activities. The most potent antioxidant peptides showed a half maximal inhibitory concentration (IC50) of 35.5 ± 0.3 µg/mL determined by 1,1-diphenyl-2-picrylhydrazyl (DPPH). They also caused a dose-dependent prolongation of the aPTT clotting time with an IC50 value of ~82 µg/mL. Interestingly, MALDI-TOF/MS analysis showed the presence of three major peptides with low molecular weights of 2257.199 Da, 2717.165 Da, and 5422.002 Da. The derived amino-acid sequence of GdAPs revealed their unique structural features, exhibiting homology with various proteins present in the genome of Arachis hypogaea. All in all, our data suggest a direct applicability of GdAPs for pharmaceutical purposes.